Desenvolvimento regional e turismo de base local: o caso do Parque Estadual de Canudos - Azevedo, Antônio José Batista de (2009)
This dissertation is a product of a bibliographic, documentary and at field research, characterized as study case, realized between 2007 and 2008, at the cities of Canudos and Salvador, to detect how to transform the Canudos State Park in a tourism product which can sustain itself, to make work and money for the citizens of Canudos and to be a service for the civic life of Bahia. Was tried to understand what is a historic, cultural and environmental park, following the Brazilian legislation, inside the context of sertanejo tourism as the best form for the development of touristic activities with the participation of the local community as beneficent and beneficiaries of all the things made on the production chain (socio-economic local) by the needs of tourism flows. Was presented a group of strategies at dimensions of short, medium and big times, to interfere on the regional dynamic, from public and private interventions in a context of participative planning envisioning the sustainable development of the Canudos War region. Was sought general and specifics objectives, hypothesis were tested and confronted with the results of researches and analysis made. Also was realized a theoric referential to support the conclusion of works. At last, was made general and final considerations about the researched objects, reaching a conclusion of the pertinency in requalify the PEC (Canudos State Park) as touristic attractive, once that this is the way these equipments on the actual world, and allows or potentiate the insertion of a poor region out of the international commercial context with sustainability. This study, yet unfinished, open ways for new academic ways to elucidation of many questions that will come along the works and will be shown from now.